Leptin acts in the carotid bodies to increase minute ventilation during wakefulness and sleep and augment the hypoxic ventilatory response. (29th November 2018) - Caballero‐Eraso, Candela; Shin, Mi‐Kyung; Pho, Huy; Kim, Lenise J; Pichard, Luis E.; Wu, Zhi‐Juan; Gu, Chenjuan; Berger, Slava; Pham, Luu; Yeung, Ho‐Yee (Bonnie); Shirahata, Machiko; Schwartz, Alan R.; et al.
Abstract : Key points: Leptin is a potent respiratory stimulant. A long functional isoform of leptin receptor, LepR b, was detected in the carotid body (CB), a key peripheral hypoxia sensor. However, the effect of leptin on minute ventilation ( V E ) and the hypoxic ventilatory response (HVR) has not been sufficiently studied. We report that LepR b is present in approximately 74% of the CB glomus cells. Leptin increased carotid sinus nerve activity at baseline and in response to hypoxia in vivo . Subcutaneous infusion of leptin increased V E and HVR in C57BL/6J mice and this effect was abolished by CB denervation. Expression of LepR b in the carotid bodies of LepR b deficient obese db/db mice increased VE during wakefulness and sleep and augmented the HVR. We conclude that leptin acts on LepR b in the CBs to stimulate breathing and HVR, which may protect against sleep disordered breathing in obesity. Abstract: Leptin is a potent respiratory stimulant. The carotid bodies (CB) express the long functional isoform of leptin receptor, LepR b, but the role of leptin in CB has not been fully elucidated. The objectives of the current study were (1) to examine the effect of subcutaneous leptin infusion on minute ventilation ( V E ) and the hypoxic ventilatory response to 10% O2 (HVR) in C57BL/6J mice before and after CB denervation; (2) to express LepR b in CB of LepR b ‐deficient obese db / db mice and examine its effects on breathing during sleep and wakefulness and on HVR. We found that leptin enhanced carotid sinus nerve activity at baseline and in response to 10% O2 in vivo . In C57BL/6J mice, leptin increased V E from 1.1 to 1.5 mL/min/g during normoxia ( P < 0.01) and from 3.6 to 4.7 mL/min/g during hypoxia ( P < 0.001), augmenting HVR from 0.23 to 0.31 mL/min/g/Δ F I O 2 ( P < 0.001). The effects of leptin on V E and HVR were abolished by CB denervation. In db / db mice, LepR b expression in CB increased V E from 1.1 to 1.3 mL/min/g during normoxia ( P < 0.05) and from 2.8 to 3.2 mL/min/g during hypoxia ( P < 0.02), increasing HVR. Compared to control db / db mice, LepR b transfected mice showed significantly higher V E throughout non‐rapid eye movement (20.1 vs . −27.7 mL/min respectively, P < 0.05) and rapid eye movement sleep (16.5 vs 23.4 mL/min, P < 0.05). We conclude that leptin acts in CB to augment V E and HVR, which may protect against sleep disordered breathing in obesity. Key points: Leptin is a potent respiratory stimulant. A long functional isoform of leptin receptor, LepR b, was detected in the carotid body (CB), a key peripheral hypoxia sensor. However, the effect of leptin on minute ventilation ( V E ) and the hypoxic ventilatory response (HVR) has not been sufficiently studied. We report that LepR b is present in approximately 74% of the CB glomus cells. Leptin increased carotid sinus nerve activity at baseline and in response to hypoxia in vivo . Subcutaneous infusion of leptin increased V E and HVR in C57BL/6J mice and this effect was abolished by CB denervation. Expression of LepR b in the carotid bodies of LepR b deficient obese db/db mice increased VE during wakefulness and sleep and augmented the HVR. We conclude that leptin acts on LepR b in the CBs to stimulate breathing and HVR, which may protect against sleep disordered breathing in obesity.